The Influence of School Climate on Teacher Innovation in Early Childhood Education Mediated by Teacher Self-Efficacy - Naili Sa'ida; Nina Veronica; Tri Kurniawati (Jurnal Pendidikan Anak, 2026)
The research aims to analyze the influence of school climate on early childhood education teachers' innovation with teachers' self-efficacy as a mediating variable. This research uses a quantitative approach with an explanatory research design. The population of early childhood education (ECE) teachers in East Java Province, with a sample of 200 teachers selected using the multistage cluster random sampling technique. Data were collected thru a questionnaire using a five-point Likert scale. Data analysis was conducted using Structural Equation Modeling (SEM). The research results indicate that the research model fits well with the empirical data (CMIN/DF = 1.284; RMSEA = 0.038; GFI = 0.934; AGFI = 0.907; CFI = 0.976; TLI = 0.968). The school climate has a positive and significant effect on teachers' self-efficacy (β = 0.620; p < 0.001), teachers' self-efficacy has a positive and significant effect on teachers' innovation (β = 0.540; p < 0.001), and the school climate has a positive and significant effect on teachers' innovation (β = 0.280; p = 0.001). Additionally, teachers' self-efficacy partially mediates the effect of school climate on teachers' innovation with an indirect effect value of 0.335 (p = 0.003). These findings indicate that a conducive school climate can enhance teachers' innovation both directly and by strengthening teachers' self-efficacy.